Symbols of the Russian criminal process - A.V. Agutin (Penza State University Publishing House, 2021)
Background. Russian shrines (the value-semantic foundations of the existence of the Russian criminal process) determine the meaning of domestic criminal proceedings. Unfortunately, the criminal procedure doctrine embodied in the Code of Criminal Procedure has adopted ideologies of liberalism that are alien to our people. In practical terms, the perception of these liberal ideologies leads to the curtailment of the meaning (nonsense) of criminal procedural activity (criminal prosecution). This largely actualized the problem of the study. The purpose of the research is to substantiate a number of provisions according to which criminal procedure activity (criminal prosecution) should be based on the value and semantic foundations of the existence of the Russian people in the form of the spiritual pillars of the Orthodox faith, cultural and historical heritage and the system of traditional spiritual and moral values. Materials and methods. The implementation of the research tasks was achieved on the basis of understanding the value-semantic existence of domestic criminal justice, the systemic influence of spiritual pillars, cultural and historical heritage and the system of traditional spiritual and moral values on the quality of criminal procedural activity (criminal prosecution). The methodological potential includes the following research methods: spiritual and cultural-historical approaches, system-activity approach and functional analysis. Russian criminal procedure symbols and the nonsense of criminal procedure activity (criminal prosecution) are understood in the article, it is established: Russian shrines (the value-semantic foundations of the Russian criminal process) determine the meaning of domestic criminal justice, and the ideologems of liberalism – the nonsense of criminal procedure activity (criminal prosecution). Conclusions. Based on the study, it was concluded: firstly, at the level of the whole, the Russian people in the criminal procedural sphere has a specific goal  criminal procedural activities should be carried out by individuals; secondly, the reproduction of nonsense in the implementation of criminal prosecution will continue until the ideological basis of Russian legislation is changed, and the ideologemes of liberalism are curtailed under the influence of the spiritual pillars of the Orthodox faith, cultural and historical heritage and the system of traditional spiritual and moral values of the Russian the people; thirdly, the spiritual bonds of the Russian people should form the value, semantic and ideological basis of the effectiveness of the ideological filter, capable of filtering out foreign and foreign concepts of criminal justice that are hostile to the Russian community.